Faith-Based Climate Advocacy and Moral Responsibility: A Cross-Religious Analysis of Community Mobilization for Environmental Justice - Yulianti Prihatiningrum; Meiske Claudia; Yoga Adi Prayogi; Ismat Valiyev (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This study explores the integration of indigenous spiritual knowledge into modern environmental ethics, focusing on the role of traditional ecological wisdom, spiritual cosmology, and stewardship practices in promoting sustainability. Indigenous worldviews often emphasize the interconnectedness between humans, the spirit world, and nature, viewing these relationships as sacred and reciprocal. This paper highlights the philosophical contributions of indigenous environmental ethics, which contrast with Western anthropocentric frameworks, offering a more holistic, spiritual, and culturally embedded perspective on ecological stewardship. Through a qualitative comparative approach, the study examines indigenous practices such as those found in the Anishinaabe philosophy of mino-mnaamodzawin and the Sarnaism faith of the Oraon community, demonstrating how spiritual connections to nature foster a deep sense of responsibility and environmental ethics. Additionally, the study discusses the challenges of integrating indigenous spiritual principles into Western academic and policy frameworks, including issues of cultural appropriation and the preservation of traditional knowledge. The research further explores potential strategies for collaboration, emphasizing community-driven approaches that respect and incorporate indigenous knowledge into global environmental governance. This integration can lead to more inclusive and sustainable environmental practices that honor both ecological balance and cultural heritage. The findings suggest that indigenous spiritual knowledge offers essential insights into creating a more sustainable and ethical approach to environmental challenges, providing a model for future policy development and global ecological strategies.